2007
DOI: 10.1097/01.meg.0000252634.26538.eb
|View full text |Cite
|
Sign up to set email alerts
|

Herb-induced hepatitis by Teucrium polium L.: report of two cases and review of the literature

Abstract: Herbal medicinal products are being increasingly used throughout the world. Herbal 'remedies' are, however, not risk free and many cases of hepatotoxicity have been reported. Teucrium polium grows mostly in the Mediterranean basin and is popular, because of hypoglycemic and hypolipidemic properties. We report two cases of T. polium-induced hepatitis in Greek female patients, who used the plant's extract to control the cholesterol levels. Both patients presented with very high aminotransferases after consuming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 22 publications
0
22
1
1
Order By: Relevance
“…Its flowers are small and range from pink to white; its leaves are used in cooking and for medicinal purposes. Hepatotoxicity due to this herb has been reported previously, but the exact mechanism of liver damage is unknown (29). One case of T. polium toxicity requiring a liver transplantation has been reported (30).…”
Section: Discussionmentioning
confidence: 97%
“…Its flowers are small and range from pink to white; its leaves are used in cooking and for medicinal purposes. Hepatotoxicity due to this herb has been reported previously, but the exact mechanism of liver damage is unknown (29). One case of T. polium toxicity requiring a liver transplantation has been reported (30).…”
Section: Discussionmentioning
confidence: 97%
“…Although, germander has been considered to be risk free, many cases of its hepatotoxic effect have been reported indeed (5,17,60,65). Teucrium poliuminduced hepatotoxicity has been observed in several cases as well (61,64,(227)(228)(229)(230). The mechanism of hepatotoxic action of germander is not well known.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of hepatotoxic action of germander is not well known. However, some studies may contribute to the hepatotoxic potential pointing to the furano neoclerodane diterpenoids constituent, found mainly in teucrin A (61,231). Accordingly, two cases reported that dual mechanisms-direct toxicity and secondary immune reactions-can mediate germander hepatotoxicity (60,232).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, while hepatic impairment, resulting from the use of conventional drugs, is widely acknowledged, there is less awareness of the potential hepatotoxicity of herbal preparations and other botanicals, many of which are believed to be harmless and are commonly used for self-medication without supervision (Stickel, Egerer, & Seitz, analgesic, antibacterial, and antidiabetic effects (Baluchnejadmojarad, Roghani, & Roghani-Dehkordi, 2005;Tariq, Ageel, Al-Yahia, Mossa, & Al-Said, 1989;Mansouri, 1999). Like other Teucrium species, it is widely popular because of its hypoglycemic and hypolipidemic properties (Esmaeili & Yazdanparast, 2004;Rasekh, Khoshnood-Mansourkhani, & Kamalinejad, 2001), but hepatitis and intrahepatic cholestatic liver disease were the etiology of liver damage following the consumption of this drug (Savvidou et al, 2007;Starakis et al, 2006). Hepatotoxicity has been ascribed to neo-clerodane diterpenoids, whose furan ring seems to be oxidized by CYP3A4 to reactive epoxides (Gori et al, 2011).…”
Section: Introductionmentioning
confidence: 99%